"You Are as You Read": Do Students' Reading Interests Contribute to Their Individuality?. Issue 1 (2nd January 2016) - Dollinger, Stephen J.
Abstract : On empirical and theoretical grounds, it is proposed that the enjoyment of reading, and particular reading interests, relate to people's individuality. This research used photo essays about the self as the method for operationalizing individuality—that is, self-construals that are unlike others (i.e. are uniquely self-reflective, multidimensional, creative). In two studies of college students (N = 689 with questionnaire data and photo essays), findings showed that, as compared to more conventional peers, individualistic photo essayists reported greater enjoyment of reading and had more "intellectual" reading interests, including fiction, the humanities/social science, and science. More conventional students preferred to read about news, sports, and romance/sexuality. Unlike stable personality traits, amount and types of reading may be one personally controllable path toward developing individuality of young adults.